2012
DOI: 10.1128/aac.06126-11
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pilot Trial of Eight Weeks of Bedaquiline (TMC207) Treatment for Multidrug-Resistant Tuberculosis: Long-Term Outcome, Tolerability, and Effect on Emergence of Drug Resistance

Abstract: The 2-year follow-up results for a randomized placebo-controlled study of 47 patients with multidrug-resistant pulmonary tuberculosis treated with either the new diarylquinoline TMC207, recently renamed bedaquiline, or placebo, added to the first 8 weeks of a background regimen, are presented. Bedaquiline significantly reduced the time to culture conversion over 24 weeks (hazard ratio, 2.253; 95% confidence interval, 1.08 to 4.71; P ‫؍‬ 0.031). With the exception of nausea reported in 26% of patients receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
274
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(297 citation statements)
references
References 12 publications
9
274
0
3
Order By: Relevance
“…292 In phase 2 trials, 2-month sputum culture conversion increased after 8-week therapy from 9% with multidrug background therapy and placebo to 48% with background therapy and bedaquiline, and the increase was sustained at 6 months. 365,366 Mortality was higher in the bedaquiline group than the placebo group, but most of the deaths in the bedaquiline group occurred after completion of the 6-month course of bedaquiline treatment, and causes of death were widely variable. This suggests that the increased mortality associated with bedaquiline in the small phase 2 study is a chance finding.…”
Section: Bedaquilinementioning
confidence: 97%
See 1 more Smart Citation
“…292 In phase 2 trials, 2-month sputum culture conversion increased after 8-week therapy from 9% with multidrug background therapy and placebo to 48% with background therapy and bedaquiline, and the increase was sustained at 6 months. 365,366 Mortality was higher in the bedaquiline group than the placebo group, but most of the deaths in the bedaquiline group occurred after completion of the 6-month course of bedaquiline treatment, and causes of death were widely variable. This suggests that the increased mortality associated with bedaquiline in the small phase 2 study is a chance finding.…”
Section: Bedaquilinementioning
confidence: 97%
“…Although encouraging initial observations have been made of faster culture conversion in early bactericidal activity and phase 2 studies of bedaquiline, 365,366 and high rates of culture conversion in French 367 and South African patients with XDR tuberculosis (100% in the French cohort and 85% in the South African cohort), 324 another analysis 368 indicated that the 120-week culture conversion rate was 70% in patients with pre-XDR tuberculosis and 62% in XDR tuberculosis when bedaquiline was used with companion drugs and an optimised background regimen. Thus, even with newer drugs such as bedaquiline, treatment failure will be common in patients with XDR tuberculosis or those with resistance beyond XDR tuberculosis, for which no effective therapy is available and so it remains programmatically incurable.…”
Section: Bedaquilinementioning
confidence: 99%
“…The study investigators later reported twoyear follow-up results of the same patient cohort, though it is important to note that the study drug (bedaquiline or placebo) had been administered only during the first eight weeks of their treatment. 19 In longitudinal follow-up, patients in the bedaquiline group experienced increased rates of culture conversion at 24 weeks, with 81% of patients in the bedaquiline group having negative sputum compared with 65% of patients in the placebo group (P = 0.03). In addition, there was a trend toward reduced acquisition of additional resistance to accompanying drugs among patients who had received bedaquiline.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] A summary of the study is presented in Table 2. In the first stage of the study, 47 patients with newly diagnosed smear-positive MDR-TB were randomized to receive bedaquiline (which at that time was referred to as TMC207) or placebo, in combination with a standard five-drug MDR-TB treatment regimen, for a period of eight weeks.…”
Section: Introductionmentioning
confidence: 99%
“…In second stage of the previous phase 2 trial, Diacon et al 28 presented the 2-year follow-up results for a RCT of 47 MDR-TB patients treated with either the bedaquiline, or placebo. These treatments were added for the first 8 weeks of a background regimen.…”
Section: Veziris Et Almentioning
confidence: 99%